ISLAMIC BANK RISK MANAGEMENT PROBLEMS AND SOLUTIONS IN UZBEKISTAN (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
this article investigates the multifaceted risk management challenges confronting Islamic banking in Uzbekistan as the country transitions from pilot initiatives to full-scale implementation following the landmark Islamic banking law enacted in early 2026. By analyzing recent regulatory advancements, including the Central Bank’s IFSB membership, AAOIFI alignment initiatives, and the planned national rollout beginning in 2027, the study highlights critical vulnerabilities in Shariah governance, liquidity provisioning for asset-backed products, operational transitions within Islamic windows, and human capital readiness amid rapid sector expansion. Ultimately, it proposes a forward-looking framework of adaptive supervisory tools, digital risk analytics, and targeted capacity-building partnerships to foster resilient, Shariah-compliant growth that enhances financial inclusion and positions Uzbekistan as a emerging hub for Islamic finance in Central Asia.